Physical Factors and Spatial Impressions of Surround Sound Recording - Kamekawa, T.; Marui, A. (2012 13th ACIS International Conference on Software Engineering, Artificial Intelligence, Networking and Parallel and Distributed Computing, 2012)
Verbal descriptors are often used on rating scales in the evaluation of spatial impression. However, in the more critical evaluation of spatial impression such as surround microphone settings, it becomes very difficult to share meanings for each perceptual attribute among the evaluators. The authors attempted to elicit common attributes from surround sound recordings by triadic elicitation procedure. Three attributes, "brightness," "temporal separability," and "spatial homogeneity," were elicited. In this paper, authors focused on "spatial homogeneity" and considered related physical parameters such as IACC (inter-aural cross correlation coefficient), τ (tau; inter-aural time difference corresponding to IACC), and ESC (ear signal correlation; defined as the correlation between left and right ears' signal). From the data measured by a dummy-head facing toward different directions (left (15°, 30°), right (15°, 30°), and front (0°)), it was suggested that the value of ESCdl, defined as ESC differences between front and the other directions at lower ESC (under 0.5), in specified some frequency bands, was related to "spatial homogeneity".